The Response Of The Northwest Atlantic'S Coupled Slope Water System To The North Atlantic Oscillation: The Beginning Of A New Regime? - Connelly, Matthew (2012)
The northwest Atlantic's slope waters respond as a coupled system to North Atlantic Oscillation-mediated differences in upstream forcing from the Labrador Current. Hydrographic responses of this Coupled Slope Water System (CSWS) typically result in warmer (colder) and saltier (fresher) slope waters during positive (negative) phases of the NAO. A regional slope water temperature (RSWT) index was developed to characterize these changes in slope-water hydrography (MERCINA, 2001). Since the 1970s, the NAO and RSWT indices have been predominantly positive, with occasional NAO phase reversals preceding drops in the RSWT index. Here, an empirical model developed for predicting the RSWT index's response to NAO forcing is explored to determine its recent performance and whether any improvements can be made. The model has performed well for the past decade, and no major improvements appear justified. In 2009, the NAO entered a multi-year period of negative index values, something that has not been observed since the 1960s. We predict that the RSWT index will respond strongly to this negative NAO forcing, resulting in a modal shift in the CSWS similar to that observed in 1998. Changes in remote forcing from the Arctic are hypothesized to be behind the recent changes in NAO behavior.